Charting the science of public affairs - Tagarino, Rogelio N. (The Journal of Public Affairs and Development, 2012)
The necessary body of knowledge and methodology for the comprehensive appreciation and understanding of public affairs for policy decision-making have remained elusive. This paper clarifies the concept of public affairs as an area for building a body of knowledge into a distinct academic science and a valuable discipline for governance. it includes brief reviews of relevant literature on public affairs; a theoretical model of public affairs as a community system; an analytical framework for the science of public affairs; and some concluding insights for building a body of knowledge of a public affairs system.